2004
DOI: 10.1523/jneurosci.5119-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting the Nogo Receptor Enhances Optic Nerve Regeneration If Retinal Ganglion Cells Are in an Active Growth State

Abstract: Mature retinal ganglion cells (RGCs), like other CNS neurons, cannot regrow injured axons into a myelin-rich environment. If stimulated by macrophage-derived factors, however, RGCs can regenerate their axons for considerable distances through the distal optic nerve. Using this "sensitized background," we investigated the effects of either increasing the expression or suppressing the activity of the Nogo receptor (NgR). NgR mediates the growth-inhibiting effects of three myelin proteins, Nogo, OMgp (oligodendro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
194
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(207 citation statements)
references
References 42 publications
12
194
0
1
Order By: Relevance
“…Adult neuronal populations upregulate regenerationassociated genes (RAGs) after axotomy (Tetzlaff et al, 1991;Schaden et al, 1994;Bonilla et al, 2002;Tanabe et al, 2003;Fischer et al, 2004), and axonal sprouting following CNS injury, including TBI, may be accompanied by reinduction of genes ordinarily associated with developmental axonal growth (Emery et al, 2000;Abankwa et al, 2002;Emery et al, 2003;Mason et al, 2003). Over-expression of SPRRR1A can promote axonal outgrowth in vitro (Bonilla et al, 2002), and following FP brain injury, we observed an increased expression of SPRR1A(+)/NeuN (+) neurons in injured cortex and, to lesser extent, CA3 of the hippocampus although frequent SPRR1A (+)/MAP-2 (−) cells were also evident.…”
Section: Discussionmentioning
confidence: 99%
“…Adult neuronal populations upregulate regenerationassociated genes (RAGs) after axotomy (Tetzlaff et al, 1991;Schaden et al, 1994;Bonilla et al, 2002;Tanabe et al, 2003;Fischer et al, 2004), and axonal sprouting following CNS injury, including TBI, may be accompanied by reinduction of genes ordinarily associated with developmental axonal growth (Emery et al, 2000;Abankwa et al, 2002;Emery et al, 2003;Mason et al, 2003). Over-expression of SPRRR1A can promote axonal outgrowth in vitro (Bonilla et al, 2002), and following FP brain injury, we observed an increased expression of SPRR1A(+)/NeuN (+) neurons in injured cortex and, to lesser extent, CA3 of the hippocampus although frequent SPRR1A (+)/MAP-2 (−) cells were also evident.…”
Section: Discussionmentioning
confidence: 99%
“…CTB-A594-positive axons were observed on longitudinal optic nerve sections (14 mm) with a Zeiss Axioskop 2 Plus microscope (Carl Zeiss, Feldbach, Switzerland) and images were taken with a CCD video camera at x 20 magnification. The number of growing axons was estimated at different distances (50,100,150,200, 300, 400, and 500 to 1000 mm) after the lesion site. Five-six optic nerve sections were analyzed per animal.…”
Section: Moreover Inflammation-inducing Agents Such As Zymosan or Pamentioning
confidence: 99%
“…However, this NgR antagonist peptide does not block the inhibitory action of a second Nogo domain located in the amino terminal region of the Nogo-A isoform (Fournier et al, 2001). Viral expression of a dominant-negative version of the NgR enhances optic nerve regeneration, especially when an enhanced growth state is induced by lens injury (Fischer et al, 2004). For MAG, null mutations do not permit CST regeneration after SCI but do enhance peripheral nerve regeneration on certain genetic backgrounds (Bartsch et al, 1995;Schafer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%